Abnormal permeability precedes the development of a gluten sensitive enteropathy in Irish setter dogs. Issue 7 (July 1991) - Hall, E J; Batt, R M
Abstract : Intestinal permeability to 51Cr-EDTA was examined during the development of gluten sensitive enteropathy in dogs bred from affected Irish setters and reared on a normal wheat containing diet. Comparisons were made with litter mates reared on a gluten free diet and with a control group of age matched, clinically healthy Irish setters reared on the normal diet. Studies at 4, 6, 8, and 12 months of age were correlated with morphometric and biochemical examinations of peroral jejunal biopsy specimens. Permeability was increased at all ages in the group fed gluten free diet compared with control dogs, although there were no differences in villus height, intraepithelial lymphocyte density, and alkaline phosphatase activity. At four months, permeability in the normal diet group was greater than in controls, although comparable with that in the gluten free diet group. Permeability in the normal diet group increased further in conjunction with the development of partial villus atrophy and reduced alkaline phosphatase activity, and by 12 months permeability was significantly greater than in their gluten free diet litter mates and the control dogs. The findings suggest that an underlying permeability abnormality may be involved in the pathogenesis of gluten sensitive enteropathy in Irish setter dogs.